Blood loss in caesarean section in Hospital Universiti Sains Malaysia (HUSM) : estimation by surgeons and anaesthetists in comparison with quantitative measurement and blood parameters assessments - Ariff @ Ghazali, Nazhan Afeef Mohd (2017)
Background: We compared the visual estimation of blood loss for Caesarean section (CS) by surgeons and anaethetists and their accuracy with relation to years of experience against quantitative measurement. Haemoglobin (Hb) trend after CS were also studied. Methods: 134 patients who underwent CS were included. Visual estimations were reported by surgeons and anaesthetists. The blood volume in collection bottle and disposable items were quantified. Hb levels pre-CS followed by 1 hour and 24 hours post CS were taken. Data were tested by Reliability Testing, Independent T-Test, Pearson’s Correlation and Multiple Linear Regressions where P <0.05 is considered significant. Results: There were strong correlation between surgeon’s and anaesthetist’s estimations of blood loss and quantitative measurement with Intraclass Correlation Coefficient of r = 0.828and r = 0.805, P <0.001. Surgeons’ accuracy in estimating blood loss has no significant difference in less and equal to 5 experience years against more than 6 experience years group, P= 0.053. Anaesthetists’ accuracy in estimating blood loss has significant difference in less and equal to 5 experience years against more than 6 experience years group, P= 0.038. There was moderate negative correlation in between percentage blood loss and Delta Hb 1 hour post CS, P <0.001. Percentage blood loss, intraoperative fluid administration and patient previous scars were strong predictors for Delta Hb 1 hour post CS with P < 0.05. Conclusions: Estimation blood loss for CS by surgeons and anaesthetists in HUSM correlates with quantitative measurement. Drop in Hb post CS correlates with percentage blood loss. Prediction of Delta Hb 1 hour and 24 hours post CS can be a useful tool in helping doctors in managing patient.